Distribution of atrial low voltage induced by vein of Marshall ethanol infusion. (4th June 2022) - Kamakura, Tsukasa; André, Clémentine; Duchateau, Josselin; Nakashima, Takashi; Nakatani, Yosuke; Takagi, Takamitsu; Krisai, Philipp; Ascione, Ciro; Balbo, Conrado; Tixier, Romain; Chauvel, Rémi; Cheniti, Ghassen; et al.
Abstract: Introduction: Systematic and quantitative descriptions of vein of Marshall (VOM)‐induced tissue ablation are lacking. We sought to characterize the distribution of low voltage observed in the left atrium (LA) after VOM ethanol infusion. Methods and Results: The distribution of ethanol‐induced low voltage was evaluated by comparing high‐density maps performed before and after VOM ethanol infusion in 114 patients referred for atrial fibrillation ablation. The two most frequently impacted segments were the inferior portion of the ridge (82.5%) and the first half of the mitral isthmus (pulmonary vein side) (92.1%). Low‐voltage absence in these typical areas resulted from inadvertent ethanol infusion in the left atrial appendage vein ( n  = 3), initial VOM dissection ( n  = 3), or a "no branches" VOM morphology ( n  = 1). Visible anastomosis of the VOM with roof or posterior veins more frequently resulted in low‐voltage extension beyond typical areas, toward the entire left antrum (19.0% vs. 1.9%, p  = .0045) or the posterior LA (39.7% vs. 3.8%, p  < .001) but with a limited positive predictive value ranging from 29.4% to 43.5%. Ethanol‐induced low voltage covered a median LA surface of 3.6% (1.9%–5.0%) and did not exceed 8% of the LA surface in 90% of patients. Conclusion: VOM ethanol infusion typically locates at the inferior ridge and the adjacent half of the mitral isthmus. Low‐voltage extensions can be anticipated but not guaranteed by the presence of visible anastomosis of the VOM with roof or posterior veins. Abstract : Low‐voltage distribution and prediction after VOM ethanol infusion.